Features of visual perception of the historical environment of the Desyatynna Church in Kyiv - Ruzhytska, Nadiia; Sydorenko, Iryna; Minder, Viktoriia; Pikhalo, Olesia (Landscape Architecture and Art, 2023)
Landscape, especially urban landscape, contributes to the formation of a sense of place. The identification of the perception characteristics of the historical image of Kyiv city, based on visual landscape research, was conducted with the aim of establishing visual connections and areas between sacred structures in the complex relief conditions of the Starokyivska Hill. The study applied methods for determining the quantitative indicators of spatial-visual characteristics of the studied locality based on a planned route survey. The parameters of the main selected points were determined by depth of visibility, horizontal viewing angle, presence of focal points, accents, types of perspectives, and types of space. Through visual landscape research, the dynamics of visual connections and areas between elements in the historical landscape of Kyiv were identified. The absence of changes in the spatial-visual characteristics was established at three selected points, while changes were found in others. Specifically, the changes are characterized by a decrease in the depth of visibility along the visual axis between the Desyatynna Church and the St. Andrew’s Church. The need to search for ways to model the outline of the landscape in the complex relief conditions of the Starokyivska Hill is revealed for the perspective of preserving the historical image and improving spatial solutions in the urban environment.